Araf51 with improved transglycosylation activities: one engineered biocatalyst for one specific acceptor. (30th January 2015) - Pennec, Alizé; Daniellou, Richard; Loyer, Pascal; Nugier-Chauvin, Caroline; Ferrières, Vincent
Graphical abstract: Highlights: A random mutagenesis of Ara f 51 affords improved biocatalysts for transglycosylation. Five efficient mutated enzymes for the synthesis of alkyl furanosides. Each selected mutant is specific for one alcohol acceptor. Abstract: A random mutagenesis of the arabinofuranosyl hydrolase Ara f 51 has been run in order to have access to efficient biocatalysts for the synthesis of alkyl arabinofuranosides. The mutants were selected on their ability to catalyze the transglycosylation reaction of p -nitrophenyl α-l -arabinofuranoside ( p NP-Ara f ) used as a donor and various aliphatic alcohols as acceptors. This screening strategy underlined 5 interesting clones, each one corresponding to one acceptor. They appeared to be much more efficient in the transglycosylation reaction compared to the wild type enzyme whereas no self-condensation or hydrolysis products could be detected. Moreover, the high specificity of the mutants toward the alcohols for which they have been selected validates the screening process. Sequence analysis of the mutated enzymes revealed that, despite their location far from the active site, the mutations affect significantly the kinetics properties as well as the substrate affinity of these mutants toward the alcohol acceptors in the transglycosylation reaction.